145k views
1 vote
How would you write the following expression as a single term? 3[2 ln(x-1) - lnx] + ln (x+1)

User Ilise
by
5.6k points

1 Answer

2 votes

Apply the rule:
n ln x = ln x^(n)


3[2 ln(x-1) - lnx] + ln(x+1)=3[ln(x-1)^(2) - lnx ] + ln(x+1)

Apply the rule :
log a - log b = log (a)/(b)


3[2 ln(x-1) - lnx] + ln(x+1)=3ln((x-1)^(2) )/(x) + ln(x+1)

Apply the rule:
n ln x = ln x^(n)


3[ln (x-1)^(2) -ln x]+ln (x+1)= ln ((x-1)^(6) )/(x^(3) ) +log(x+1)

Finally, apply the rule: log a + log b = log ab


3[ln(x-1)^(2) -ln x]+log(x+1)=ln((x-1)^(6)(x+1) )/(x^(3) )

User LogicaLInsanity
by
5.4k points